Bayesian based lifetime prediction for high-power white LEDs. (15th December 2021) - Ibrahim, Mesfin S.; Jing, Zhou; Yung, Winco K.C.; Fan, Jiajie
Highlights: Traditional NLS regression-based standards showed higher prediction inaccuracy. Accelerated degradation test designed to collect lumen degradation data for LEDs. A probabilistic estimation of model parameters with a Bayesian method is presented. Applied on two case studies of LED packages and lamps to validate proposed method. Proposed method showed an improved accuracy compared with TM-21 and TM-28 methods. Abstract: The introduction of high-power white LEDs has revolutionized the lighting industry in the past few decades due to the multiple benefits in terms of high reliability, environmental friendliness and versatile applications. However, challenges have arisen in assessing the reliability and lifetime prediction because it is difficult to record the failure data in a short period of time. Currently, the nonlinear least squares (NLS) regression-based method is used in industry for projecting the lumen maintenance lifetime from degradation data. The model parameters estimated using the NLS regression approach are deterministic and introduce high prediction errors. In this paper, a Bayesian method is proposed to estimate the remaining useful lifetimes (RULs) of both high-power white LED packages and lamps. The accelerated degradation tests conducted for gathering lumen degradation data are used to validate the proposed method. The exponential decay model is used as the degradation model and the parameters are estimated based on Markov Chain Monte Carlo (MCMC) sampling and using the Metropolis-Hasting (MH) algorithm. The lifetime prediction results showed that the Bayesian method has better prediction accuracy compared to the NLS method. Thus, the proposed Bayesian method is shown to be a promising approach to address the lifetime prediction issue for high-power white LEDs with improved prediction accuracy.